Dosimetric Feasibility of Dose Escalation Using SBRT Boost for Stage III Non-Small Cell Lung Cancer - Hepel, Jaroslaw T.; Peter, Justin; Hiatt, Jessica R.; Patel, Salil; Osibanjo, Oluwademilade; Safran, Howard; Curran, Bruce; DiPetrillo, Thomas (Frontiers in Oncology, 2012)
Abstract: Purpose: Standard chemoradiation therapy for Stage III non-small cell lung cancer results in suboptimal outcomes with a high rate of local failure and poor overall survival. We hypothesize that dose escalation using stereotactic body radiotherapy (SBRT) boost could improve upon these results. We present here a study evaluating the dosimetric feasibility of such an approach. Methods: Anonymized CT data sets from 3 randomly selected patients with stage III NSCLCa undergoing definitive chemoradiation therapy in our department with disease volumes appropriate for SBRT boost were selected. 3D-CRT plans to 50.4 Gy in 28 fractions were generated follow by SBRT plans to two dose levels, 16 Gy in 2 fractions and 28 Gy in 2 fractions. SBRT plans and total composite (3D-CRT and SBRT) were optimized and evaluated for target coverage and dose to critical structures; lung, esophagus, cord, and heart. Results: All three plans met predetermined target coverage and normal tissue dose constraints. PTV V95 was equal to or greater than 95% in all cases. The cumulative lung V20 and V5 of the combined 3D-CRT and SBRT plans were less than or equal to 30% and 55%, respectively. The 5cc esophageal dose was less than 12 Gy for all low and high dose SBRT plans. The cumulative dose to the esophagus was also acceptable with less than 10% of the esophagus receiving doses in excess of 50 Gy. The cumulative spinal cord dose was less than 33 Gy and heart V25 was less than 5%. Conclusion: The combination of chemoradiation to 50.4 Gy followed by SBRT boost to gross disease at the primary tumor and involved regional lymph nodes is feasible with respect to normal tissue dose constraints in this dosimetric pilot study. A phase I/II trial to evaluate the clinical safety and efficacy of this approach is being undertaken.